EFIKASI DIRI SEBAGAI MEDIASI PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN MOTIVASI BERWIRAUSAHA TERHADAP MINAT BERWIRAUSAHA MAHASISWA - Ratna Rahayu Nengseh; Riza Yonisa Kurniawan (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2021)
AbstractEntrepreneurship education, entrepreneurial motivation, and self-efficacy play an important role in fostering student interest in entrepreneurship. The purpose of this study was to analyze the effect of entrepreneurship education and entrepreneurial motivation on college students' interest in entrepreneurship with self-efficacy as a mediating variable. This research used a quantitative approach with associative research type. The sample in this study were 135 students. This study used a questionnaire instrument to obtain data which was then analyzed using Structural Equation Modeling (SEM) analysis techniques with the WarpPLS 5.0 approach. The results showed that: (1) Entrepreneurship education has a significant and positive effect on students' interest in entrepreneurship; (2) Entrepreneurial motivation does not have a significant and positive effect on students' interest in entrepreneurship; (3) Self-efficacy has a significant and positive effect on students' interest in entrepreneurship; (4) Entrepreneurship education has a significant and positive effect on student self-efficacy; (5) Entrepreneurial motivation has a significant and positive effect on student self-efficacy; (6) Entrepreneurship education has a significant and positive effect on students' interest in entrepreneurship through self-efficacy; and (7) Entrepreneurial motivation has a significant and positive effect on students' interest in entrepreneurship through self-efficacy.Keywords: Entrepreneurial Motivation, Entrepreneurship Education, Interest In Entrepreneurship, Self-Efficacy.